Ibulina Enterprise / Saiyidah Aqilah Muhammad Hatta, Nur Najwa Awatif Yusri, Erra Shahira Ishak, Nur Ameera Dayiana Iskandar and Sara Najihah A. Jalil - Muhammad Hatta, Saiyidah Aqilah; Yusri, Nur Najwa Awatif; Ishak, Erra Shahira; Iskandar, Nur Ameera Dayiana; A. Jalil, Sara Najihah (2019)
Butter is a dairy product with high butterfat content which is sold when chilled and at room temperature in some regions, and liquid when warmed. It is made by churning fresh or fermented cream or milk to separate the butterfat from the buttermilk. It is generally used as a spread on plain or toasted bread products and a condiment on cooked vegetables, as well as in cooking, such as baking sauce making, and pan frying. Butter consists of butterfat, milk proteins and water, and often added salt.